CO2 capture on NiO supported imidazolium-based ionic liquid - Tengku Azmi, Tengku Sharifah Marliza; Yarmo, Mohd Ambar; Lahuri, Azizul Hakim; Abu Tahari, Maratun Najiha; Mohamed Hisham, Mohamed Wahab; Yap, Taufiq Yun Hin (AIP Publishing, 2016)
CO2 capture on NiO supported imidazolium-based ionic liquid, NiO/[emim][HSO4]/SiO2 as an adsorbent was investigated using gas adsorption analyzer and physicochemical properties of the adsorbent were characterized using X-ray powder diffraction (XRD), surface area analyzer (BET method) and temperature-program-desorption analysis (TPD). Immobilization of ionic liquid on silica, [emim][HSO4]/SiO2 slightly decreased the surface area compared to bare silica from 266 to 256 m2/g due to the pore blocking by the confinement of IL in SiO2 pore. Interestingly, introduction of NiO on supported ionic liquid, NiO/[emim][HSO4]/SiO2 was increased the surface area as well as pore volume from 256 to 356 m2/g and 0.14 to 0.38 cm3/g, respectively. The enhancement of surface area and pore volume was significantly increased the CO2 adsorption performance with capacity of 48.8 mg CO2/g adsorbent compared to [emim][HSO4]/SiO2 27.3 mg CO2/g adsorbent).